Peluang Investasi, Pendanaan Perusahaan, dan Kebijakan Dividen (Universitas Kadiri, 2022)
This study aims to analyze the effect of investment opportunities and corporate financing on dividend policy. The data used in this study are companies that are included in the LQ-45 index listed in Indonesia`s Stock Exchange in 2012 - 2018 with a total of 224 observations obtained from the annual financial reports of each company with access to the website www.idx.com. The analytical method used is Ordinary Least Square (OLS) and as a robustness test using Maximum Likelihood Estimation (MLE). The results found contrary to previous studies, that investment opportunities have a positive effect on dividend policy. Corporate Financing has a negative effect on dividend policy. This research can be used as a consideration for investors in expecting dividends when investing on LQ-45 companies in Indonesia`s Stock Exchange.